Integration of the Resource-Based View, Resource Dependence Theory, Dynamic Capabilities, Social Cognitive Theory, and Firm Performance Theory in Explaining the Performance of Digital MSMEs in Indonesia - Ade Alfarisi; Yayan Hendayana (Dinasti International Journal of Education Management and Social Science, 2025)
Digital transformation has changed the global business landscape and requires Micro, Small, and Medium Enterprises (MSMEs) in Indonesia to strengthen their competitiveness through resource-based strategies and adaptive innovation. This article aims to integrate five key theories in strategic management to explain the performance of digital MSMEs, namely: (1) Firm Performance Theory, which assesses organizational success multidimensionally through the Balanced Scorecard; (2) Resource-Based View (RBV), which emphasizes the importance of valuable, rare, difficult to imitate, and organized resources; (3) Resource Dependence Theory (RDT), which highlights the management of external dependencies on suppliers, customers, and institutions; (4) Dynamic Capabilities (DC), which explains the process of sensing, seizing, and reconfiguring resources to adapt to environmental changes; and (5) Social Cognitive Theory (SCT), which emphasizes the role of self-efficacy and collective efficacy as drivers of entrepreneurs’ innovative behavior. The literature review shows that RBV provides an internal foundation, RDT connects organizations with external resources, DC serves as a bridge for strategic adaptation, SCT provides behavioral microfoundation, and performance theory provides a measure of organizational success. This article identifies research gaps in multi-level and longitudinal integration and proposes a research agenda based on a mediation-moderation model to strengthen the performance and sustainability of digital MSMEs in Indonesia.